2023
DOI: 10.1186/s41747-023-00340-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between thoracic and third lumbar CT-derived muscle mass and density in Caucasian patients without chronic disease: a proof-of-concept study

Abstract: Background Computed tomography (CT) is increasingly used in the clinical workup, and existing scan contains unused body composition data, potentially useful in a clinical setting. However, there is no healthy reference for contrast-enhanced thoracic CT-derived muscle measures. Therefore, we aimed at investigating whether there is a correlation between each of the thoracic and third lumbar vertebra level (L3) skeletal muscle area (SMA), skeletal muscle index (SMI), and skeletal muscle density (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For fat tissue, a study has shown that a thinner slice increased SFA by 0.2%, VFA by 3%, and IMFA by 17.3% [ 57 ]. One could speculate whether slice thickness has a clinically relevant impact on body composition measurements as differences are minor and fall within the expected uncertainties of manual or semi-automated segmentation with intra-analyst variation described in other studies [ 35 , 40 ]. An improvement could be to resample with the same slice thickness using fully automated solutions to save precious staff resources and avoid inter and intra-rater variations and intra-patient variability in measurements [ 58 ].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…For fat tissue, a study has shown that a thinner slice increased SFA by 0.2%, VFA by 3%, and IMFA by 17.3% [ 57 ]. One could speculate whether slice thickness has a clinically relevant impact on body composition measurements as differences are minor and fall within the expected uncertainties of manual or semi-automated segmentation with intra-analyst variation described in other studies [ 35 , 40 ]. An improvement could be to resample with the same slice thickness using fully automated solutions to save precious staff resources and avoid inter and intra-rater variations and intra-patient variability in measurements [ 58 ].…”
Section: Discussionmentioning
confidence: 53%
“…The data collection period was limited to these specific time periods because of comparable standardised trauma CT protocols. The European study population from the Northern Region Denmark was previously described in detail by Brath et al [ 40 ].…”
Section: Methodsmentioning
confidence: 99%